PERTUMBUHAN DAN HASIL RUMPUT Brachiaria humidicola YANG DIBERI PUPUK KANDANG AYAM DAN NPK PADA TANAH BERPASIR (Growth and Yield of grass Brachiaria humidicola given chicken manure and NPK fertilizer on sandy soil): Winarti, S.,1) dan Kristina 2) - Administrator Journal (Fakultas Pertanian Universitas Palangka Raya, 2018)
ABSTRACTThis study aims to determine the growth and yield of grass Brachiaria humidicola on sandy soil.The design used Randomized Block Design arranged in a factorial pattern consists of two factors.The first factor was dosage of chicken manure consisting of three levels of 0, 20 and 30 t ha-1 andthe second factor was the dosage of N-P-K fertilizer consisting of four levels ie 0, 125, 250 and 500kg ha-1. The results showed that the application of manure with doses of 30 t ha-1 of grassBrachiaria humidicola grew tended to be higher, and N-P-K fertilizer with doses of 500 kg ha-1number of tiller per real clump (49,50 tillers) tends to be higher (124,9 cm) N-P-K fertilizer withdosage of 500 kg ha-1, without manure obtained fresh plant weight grass Brachiaria humidicolahighest 5.807 g m-2Keywords: Brachiaria humidicola grass, manure and N-P-K, sandy soil